Analisa Koordinasi Isolasi Peralatan di Gardu Induk Teling 70 kV - Brando Alexsander; Lily S. Patras; Fielman Lisi (Universitas Sam Ratulangi, 2018)
Abstract Along with the development of the era, the need for electrical energy continues to increase, with the increasing demand for electrical energy, the power system must also be adequate for the reliability of power systems can also grow. In the substation there is a setting of coordination Isolation. The Isolation must be planned and arranged appropriately, so that the isolation coordination within the substation can work optimally.Isolation planning in the Parent Station Teling, aims to create a system whose parts, respectively and each other have an insulation resistance such that in every operational condition the quality of service / supply of electricity can be achieved with a minimum cost possible. This analysis is used to improve high security and economical prices work by limiting the surge of over voltage and discharge to the ground and must be able to drain without making equipment damage. Keywords: arrester, BIL, coordination of isolation, over voltage AbstrakSeiring dengan berkembangnya zaman, kebutuhan akan energy listrik terus meningkat, dengan meningkatnya kebutuhan akan energy listrik maka sistem tenaga listrik juga harus memadai agar kehandalan sistem tenaga listrik juga dapat berkembang. Dalam gardu induk terdapat settingan koordinasi Isolasi. Perhitungan harus direncanakan dan diatur dengan tepat, agar koordinasi isolasi yang berada dalam gardu induk dapat bekerja optimal. Perhitungan Isolasi di Gardu Induk Teling, bertujuan untuk menciptakan suatu sistem yang bagian-bagiannya,masing-masing dan satu sama lainnya mempunyai ketahanan isolasi yang sedemikian rupa sehingga dalam setiap kondisi operasi kualitas pelayanan/penyedian tenaga listrik dapat dicapai dengan biaya yang seminimum mungkin. Analisa ini digunakan untuk meningkatkan keamanan yang tinggi dan harga yang ekonomis bekerja dengan membatasi surja tegangan lebih dan mengalirkannya (discharge) ketanah dan harus mampu mengalirkan tanpa membuat peralatan mengalami kerusakan.Katakunci : arrester, BIL, koordinasi isolasi, tegangan lebih,